The impacts of wind energy generation on the economic growth: a dynamic panel data analysis. (2nd June 2022) - Apaydın, Şükrü; Koç, Ümit
Energy is a crucial factor in both production and consumption processes. It is a critical component not only for economic growth but also for social, technological and environmental issues. With the events and facts in these areas, the importance of the energy has increased more and the research for alternative energy sources has accelerated in the last 50 years. Renewable energy sources have become more preferable by considering the goal of sustainable growth. In this context, wind energy production, which is almost the half of the total renewable energy production, has gained significant importance especially in the post-1990 period. The objective of this study is to assess the impact of wind energy production on economic growth with GMM method on a sample of 60 countries between the time period 1990 and 2017 (N = 60, T = 28). The findings suggest that wind energy positively affects economic growth, thus, supporting the growth hypothesis.